Computer-game instructional design model - Mahmud, Rosnaini; Abdullah, Yusri; Ab. Jalil, Habibah; Mohd Daud, Shaffe (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Computer game-based learning is gaining interest from academicians nowadays. The ability of computer games to motivate and engage learners has been identified by current and past researches. The positive effect of computer game to the learning environment has contributed to the rapid development of educational computer games. Researches show that to develop a good educational computer game, the development process needs to apply the computer game concept and elements, as well as a good instructional design. Generally, computer game developers tend to focus more into the game mechanics that underlie the rules of the game, while, instructional designers focuses more on the delivery of learning materials. Thus, an educational computer game development model that incorporates the concept of instructional design with computer game design is very much needed by the developers of educational computer games. This article proposes a model of educational computer game development based on ADDIE model and adapted to the concept and elements of computer games.